Analisis Kompetensi Kewirausahaan, Jiwa Kewirausahaan, Modal Usaha Terhadap Keberhasailan Usaha: Survei pada UMKM Rumah Makan di Kota Sukabumi - Cindy Fitriya; R Deni Muhammad Danial; Dicky Jhoansyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Culinary restaurant UMKM is one of the leading sectors in Indonesia that has great potential. However, currently the contribution given to the economy in Indonesia is decreasing. One of the factors causing this problem is due to declining performance. The purpose of this study was to determine the effect of entrepreneurial competence, entrepreneurial spirit, and business capital on business success. The research method uses a quantitative descriptive associative approach. The population in this study was 91 Restaurant UMKM in Sukabumi City with a sample framework using purposive sampling techniques. This study uses SPSS for data processing and hypothesis testing. Based on the results of the study, it shows that there is a negative influence between entrepreneurial competence and business success. Entrepreneurial spirit has a positive and significant effect on business success. And business capital has a positive and significant effect on business success.